Evaluation of Correlative Factors between Destructive and Non- Destructive Tests of Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
The assessment of new and old structures requires spending money to recognize the actual state for safe using them and to satisfy that the using of nondestructive testing become a favored tool to be applied for the function and quality control for the structures. One of the most effective and least costly methods is using Ultrasonic Pulse Velocity (UPV) method. The target of this paper is to find a mathematical relationship between the Ultrasonic Pulse Velocity (UPV) and the compressive strength of concrete. Therefore, the important variables which have a sensible effect on this relationship shall be investigated. These parameters include the test type of UPV testing method (direct, semi direct, indirect), concrete strength.To achieve the goal of this paper, an experimental study has been conducted to preparation six different concrete mixtures (from C20 to C45) at casting the specimens which consist of 6 concrete blocks of dimension 40×40×100 cm and for each one 9 cubes are cast of size 15 cm which has been tested at ages of 7, 28, and 60 days. For the obtained results, a statistical experimental program has been carried out in order to establish a fairly accurate relation between the ultrasonic pulse velocity and the concrete compressive strength using both MathLab and Microsoft Excel programs for extracting and plotting the final relationship models.From the obtained results, the relationships between the direct UPV, semi direct UPV, and indirect UPV in the concrete blocks and cubes with the compressive strength of concrete were found. It is found that the type of an equations is exponential type which has the similar trend of  given a relationship of ACI committee 228so these results indicate that direct, semi direct, and indirect model methods can be used to assess the actual state of in-situ structures.The direct UPV is 5% and 8.7 % higher than the average semi direct and indirect UPV respectively. Moreover, the small UPV paths give higher overestimations of concrete strength. Finally, the suggested equation in this paper is compared with the other researcher's equations to indicate the accuracy using a verification study.